Module 1: Personal Identification. Module 2: Hobbies and Interests: Elementary - Pre-Intermediate. Pre-Intermediate - Intermediate - Малетина Л. В. (General English for Technical Students)
Экспериментальное пилотирование модульной программы в 2005/2006 учебном году: на англ. яз.